PREVENTION OF SEVERE INFECTIONS IN PATIENTS WITH GENETIC DISORDERS OF THE COMPLEMENT SYSTEM REGULATION TREATING WITH ECULIZUMAB: PRESS RELEASE ON THE INTERDISCIPLINARY EXPERT COUNCIL MEETING - Editorial article (Union of pediatricians of Russia, 2017)
.